A Gendered Imperative: Does Sexual Violence Attract UN Attention in Civil Wars?. (January 2020) - Benson, Michelle; Gizelis, Theodora-Ismene
There is increasing awareness that sexual violence is distinct from other aspects of civilian victimization in civil wars. Few studies have examined the independent impact of such violence on responses to civil wars as compared to "traditional" forms of violence. This article explores whether reports of high levels of rape and sexual violence increase the probability of United Nations (UN) attention to conflicts and calls to action. In so doing, we combine original data on UN Security Council (UNSC) resolutions with data on sexual violence in armed conflict and estimate the impact of sexual violence on UN attention to all civil wars from 1990 to 2009. We show that the effects of sexual violence on the number and level of UNSC resolutions are significant even when controlling for other important determinants of UN action. These findings have important implications for understanding how the UN has expanded its view on protecting civilians.